2022
DOI: 10.3389/fnagi.2022.909582
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of 24-h Ambulatory Blood Pressure on Cognitive Function and Neuropathological Biomarker in Patients With Alzheimer's Disease

Abstract: PurposeThis study aimed to investigate the influence of 24-h ambulatory blood pressure (BP) on cognitive function and neuropathological biomarkers in patients with Alzheimer's disease (AD) at the stages of mild cognitive impairment (MCI) and dementia.MethodsThe patients with AD were divided into the MCI (AD-MCI) group and the dementia (AD-D) group. Notably, 24-h BP variables, including BP level, coefficient of variation (CV) of BP, and pulse pressure, were collected and compared between the two groups. The cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…Associations of BPV with neurodegeneration markers may depend on the choice of BPV index. Visit-to-visit variability is relatively consistently linked to AD biomarkers across different patient populations [12,28,29,31], whereas shorter-term BPV (i.e., day-to-day or 24-h) generally did not relate to tau or A␤ in previous studies [15,16], including this current report. Yet, minute-to-minute variability has been associated with plasma A␤, though not p-tau181, among 54 community-dwelling participants with a low vascular disease burden [13].…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Associations of BPV with neurodegeneration markers may depend on the choice of BPV index. Visit-to-visit variability is relatively consistently linked to AD biomarkers across different patient populations [12,28,29,31], whereas shorter-term BPV (i.e., day-to-day or 24-h) generally did not relate to tau or A␤ in previous studies [15,16], including this current report. Yet, minute-to-minute variability has been associated with plasma A␤, though not p-tau181, among 54 community-dwelling participants with a low vascular disease burden [13].…”
Section: Discussioncontrasting
confidence: 49%
“…Several prior studies have investigated associations between BPV and tau or A␤, some of which found significant associations [12][13][14][28][29][30], whereas others did not [15,16,31]. These discrepancies may be explained by substantial differences in study populations, the choice of BPV index, and the technique for biomarker measurements across studies, which hamper proper comparison of study results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation